Isolation and Characterization of Antitumor Alkaloid from Poppy Capsules (Papaver somniferum) - Ibrahim Bulduk; Fulya Taktak (Journal of Chemistry)
Noscapine, a phthalideisoquinoline alkaloid derived from opium, has been used in the treatment of various cancer types. Its low-toxicity profile has increased attention to this alkaloid. With regard to increasing demand for this compound, we developed a new method for isolation of noscapine from dried capsules of Papaver somniferum. Noscapine was successfully isolated from poppy capsules for the first time and the purity of the isolated compound was determined to be over 99.59% by HPLC analysis. The structure of noscapine was confirmed by 1H NMR, 13C NMR, FT-IR, elemental analysis, and HR-ESI-MS methods.